THE EFFECT OF LOCUS OF CONTROL AND WORK-LIFE BALANCE ON AUDITOR PERFORMANCE WITH WORK MOTIVATION AS A MODERATOR - Nyoman Juniari Arsandi; Made Yenni Latrini (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Auditor performance is a crucial element in maintaining accountability in public financial management conducted by audit entities in the Province of Bali (referred to as XYZ). In performing their duties, auditors frequently face high-pressure environments and complex situations that may impact their performance. This study aims to examine the effect of locus of control and work-life balance on auditor performance, as well as the moderating role of work motivation on these effects. The study was conducted empirically on auditors at the XYZ Representative Office in Bali Province. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that locus of control has a significant positive effect on auditor performance, and work-life balance also exerts a significant positive effect on auditor performance. Furthermore, work motivation is proven to strengthen the effect of locus of control on auditor performance, as well as the effect of work-life balance on auditor performance. This study is expected to contribute to the development of behavioral accounting theory, particularly regarding psychological factors affecting auditor performance, and to provide practical implications for the management of XYZ Representative Office in Bali in their efforts to improve auditor performance.